Порівняльна ефективність акарицидних препаратів при саркоптозі свиней - Шендрик, Любов Іванівна; Shendryk, Ljubov; Shendrik, L.; Shendryk, L. I.; Бібен, Іван Андрійович; Biben, I.; Biben, I. A.; Biben, Ivan; Куценко, С. І.; Kutsenko, S. (Львівська державна академія ветеринарної медицини ім. С. З. Ґжицького, 2001)
У представленій роботі описано порівняльну лікувальну та економічну ефективність акарицидних препаратів за виникнення саркоптозу свиней. In represented work seen out on effectiveness comparison acaricids of preparations benzil-benzoat and butoks in dreeding 1:1000 and 1:2000 attached to pigs sarcoptoses. The reseaches result showed that most effective found oneself fatherland to preparation benzil-benzoat in appearance 20%-ache to emulsion (EE=100%) attached to single his application, less effective butoks 1:2000 (EE=87,5%), emploed twice with space 7 days and shot-lived effect was attached to single use butoks 1:1000 (EE=62,5%).
Comparative effectiveness acaricids of preparations attached to pigs sarcoptoses
Keywords: саркоптоз свиней; pigs sarcoptosis; акарицидні препарати; acaricidal preparations; захворювання тварин; animal diseases; ветеринарні заходи; veterinary measures